1999
DOI: 10.1111/j.1572-0241.1999.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Multidisciplinary Evaluation of Premenopausal Women With Iron-Deficiency Anemia

Abstract: Significant upper gastrointestinal disease is identifiable among most premenopausal women with IDA (18 of 19 or 95%), even when careful evaluation by a specialist in gynecology suggests a gynecological source. Upper endoscopy should be considered in the evaluation of all premenopausal women with IDA expressing digestive complaints or in those with IDA refractory to iron supplementation. Lower endoscopic examination may be reserved for those women with symptoms or signs suggestive of colorectal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 17 publications
4
42
0
Order By: Relevance
“…One of twelve patients who underwent colonoscopy had pancolitis; the remaining 11 patients had lower gastrointestinal findings that were not responsible for IDA. The investigators of this study concluded that upper endoscopy should be considered in the evaluation of all premenopausal women with IDA who have digestive complaints or who have anemia that is refractory to iron supplementation [6].…”
Section: Discussionmentioning
confidence: 99%
“…One of twelve patients who underwent colonoscopy had pancolitis; the remaining 11 patients had lower gastrointestinal findings that were not responsible for IDA. The investigators of this study concluded that upper endoscopy should be considered in the evaluation of all premenopausal women with IDA who have digestive complaints or who have anemia that is refractory to iron supplementation [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, even in young women with iron deficiency intervention, then further evaluation may be warranted before a lengthy wait for a hematologic response. Postfelt secondary to menstrual bleeding, occult gastrointestinal bleeding and hemorrhagic gastrointestinal pathology treatment observation is also confounded by the blackening of stools from the administration of medicinal can be demonstrated in a substantial proportion and should be looked for [23]. Finally, it might be argued iron and the inability to discern melena from bleeding.…”
Section: Impact Of Fob Testing On Diagnostic Algorithmsmentioning
confidence: 99%
“…Menstrual bleeding is by far the most common explanation for excessive nongastrointestinal blood loss and acIron deficiency results from inadequate procurement of iron (due either to an iron-poor diet or to iron malab-counts for the majority of iron deficiency among premenopausal women [12,16,23]. Blood loss leading sorption) or from excessive loss of iron through bleeding.…”
Section: To What Extent Does Occult Gastrointestinal Bleeding Cause Imentioning
confidence: 99%
See 2 more Smart Citations